the determinant of cash holding in property and real estate companies - Putu Novitasari; Afrizal Nilwan; Aminah Aminah (Cita konsultindo, 2024)
To ensure the smoothness of the compani’s operational activities and maintain liquidity, the company needs to maintain an optimal cash reserve to meet financing needs. This study investigates the impact of NWC, CapEx and Profitability (ROA) on the level of Cash Holding in Property and Real Estate sector companies during the period of 2020-2022. The research uses 194 data samples from 66 Property and Real Estate sector companies listed on the IDX and selected using purposive sampling method. The type of research used descriptive method through a number-based approach. The data analysis method applied is multiple linear analysis techniques by utilizing the SPSS version 18 apllication. The test show that Net Working Capital and Profitability (ROA) partially have a positive and significant effect on Cash Holding in Property and Real Estate companies. Meanwhile, the Capital Expenditure variable partially does not show a signifiant impact on Cash Holding in Property and Real Estate firm.